Immune Status of Asymptomatic HIV-Infected Hemophiliacs: Randomized, Prospective, Two-Year Comparison of Treatment with a High-Purity or an Intermediate-Purity Factor VIII Concentrate - Mannucci, P M; Gringeri, A; de Biasi, R; Baudo, F; Morfini, M; Ciavarella, N (Thrombosis and Haemostasis, 1992)
It has been postulated that high-purity factor VIII (FVIII) concentrates, since they contain less alloantigenic proteins than intermediate-purity concentrates, might cause lesser deterioration of the immune systems of hemophilic patients infected with the human immunodeficiency virus (HIV). To evaluate this hypothesis, we have prospectively compared T-lymphocytes subsets and delayed hypersensitivity reactions to skin tests in 17 asymptomatic HIV-positive hemophiliacs randomly assigned to continue treatment with an intermediate-purity concentrate with those of 16 hemophiliacs changed to a high-purity concentrate. For both groups, during the 24-month follow-up period CD4 cell counts showed similar rates of fall from baseline values. There was also no difference in the number of patients anergic to skin tests. Three patients treated with the intermediate purity concentrate and one treated with the high-purity concentrate developed symptoms of HIV infection. On the whole, no striking benefit is conferred to the immune status of asymptomatic HIV-positive hemophiliacs by using this high-purity concentrate for 2 years.